Conductivity and dielectric studies of Li3+-irradiated PVP-based polymer electrolytes. (October 2018) - Singh, Divya; Kanjilal, D; Laxmi, GVS; Singh, Pramod K; Tomar, SK; Bhattacharya, Bhaskar
Poly(vinylpyrrolidone) (PVP) complexed with sodium iodide (NaI) is synthesized to investigate the ionic conductivity of alkaline-based polymer electrolytes. In this article, we report the modification of electrical properties of a new ion-conducting polymer electrolyte, namely, PVP complexed with NaI. Modification of polymer electrolyte was carried out before and after the exposure of films by bombarding them at different fluences with respect to Li 3+ ion beam at 60 MeV. The preparation and detailed characterization of PVP:NaI is being reported. Further, a correlation with conductivity and dielectric constant has also been established. The modulation in the conductivity is explained in terms of number of charge carriers ( n ) and its mobility ( μ ), which confirms the behavior of the polymer electrolyte as an alternative strategy to improve the conductivity.